Enabling Technologies for the Navigation and Communication of UAS Operating in the Context of BVLOS - Politi, E.; Purucker, P.; Larsen, M.; Reis, R.J. Dos; Rajan, R.T.; Penna, S.D.; Boer, J.F.; Rodosthenous, P.; Dimitrakopoulos, G.; Varlamis, I. (MDPI, 2024)
Unmanned Aerial Systems (UAS) have rapidly gained attraction in recent years as a promising solution to revolutionize numerous applications and meet the growing demand for efficient and timely delivery services due to their highly automated operation framework. Beyond Visual Line of Sight (BVLOS) operations, in particular, offer new means of delivering added-value services via a wide range of applications. This "plateau of productivity" holds enormous promise, but it is challenging to equip the drone with affordable technologies which support the BVLOS use case. To close this gap, this work showcases the convergence of the automotive and aviation industries to advance BVLOS aviation for UAS in a practical setting by studying a combination of Commercial Off-The-Shelf (COTS) technologies and systems. A novel risk-based approach of investigating the key technological components, architectures, algorithms, and protocols is proposed that facilitate highly reliable and autonomous BVLOS operations, aiming to enhance the alignment between market and operational needs and to better identify integration requirements between the different capabilities to be developed. Keywords: UAS; UAVs; BVLOS; communication systems; autonomous navigation